X-linked Juvenile Retinoschisis in a Young Female - Ranabhat, Sudha; Byanju, Raghunandan; Khadka, Simanta (Journal of Nepal Health Research Council, 2022)
X-linked juvenile retinoschisis has recessive inheritance which occurs due to RS1 gene mutation. We report an instance in a female managed with systemic and topical carbonic-anhydrase inhibitors.18-year female presented with bilateral blurred vision for two years. Best corrected vision was 6/24 right eye and 6/12 left eye. Fundus examination, ocular coherence tomography and fundus fluorescein angiography supported the diagnosis. Systemic and topical carbonic-anhydrase inhibitors were advised and followed for six months with scrutinization of possible adverse drug reaction.Juvenile retinoschisis being rare among females, prompt diagnosis and management helps for the restoration of the vision and foveal anatomy.Keywords: Carbonic anhydrase inhibitors; female; retinoschisin ; X linked juvenile retinoschisis.